Comparative study of syntactic maturity indexes between pre and post-internet generations - Bartolomé Rodríguez, Rocío (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This work shows a comparative analysis of the syntactic maturity indexes between students of the 90s of the last century and students who have grown up in the digital age, born in the years 1996, 2000 and 2004. The main hypothesis is that the average of syntactic maturity indexes would have decreased slightly in the post-internet generation due to the speed of writing and the immediacy of response used in the language of ICT. A total of 382 essays written by students in the 4th year of Primary Education (9-year-olds), the 2nd year of Compulsory Secondary Education (13-year-olds) and the 2nd year of Baccalaureate (17-year-olds) have been analyzed. The results show that the post-internet generation obtains higher rates in most of the parameters studied. Hence, it is concluded that exposure to ICT does not negatively affect the syntactic maturity of students in the quantitative terms examined
Keywords: ICT; written composition; primary and secondary indexes; unit-t